Imaging of periocular basal cell carcinoma using en face optical coherence tomography: a pilot study. Issue 10 (1st June 2010) - Khandwala, M; Penmetsa, B R; Dey, S; Schofield, J B; Jones, C A; Podoleanu, A
Abstract : Aim: To use en face optical coherence tomographic (OCT) imaging to identify features of tumour tissue and their correlation with histopathologic findings and to assess the effect of different wavelengths and resolutions of OCT in identifying tumour boundaries and features. Methods: Excision specimens of consecutive biopsy-proven periocular basal cell carcinomas (BCCs) (n=8) were assessed by OCT, performing in vitro cross-section and en face scans of the tissues. Images were collected from three different machines: systems 1 and 2 had a wavelength of 1300 nm, and system 3 had a wavelength of 840 nm. System 2 used high numerical aperture interface optics that determines higher magnification and hence allows higher transversal resolution. All the eight specimens subsequently underwent routine histopathologic examination. Results: Three common features of tumour tissue were observed in all the three systems: (1) lobular pattern of abnormal architecture, (2) dilated blood vessels and (3) high reflective margins. We compared the three systems based on their ability to pick up the three above-mentioned tumour features. In this respect, system 2 had the highest capability in picking up feature 1, followed by systems 1 and 3. In feature 2, similar results were obtained with all the three systems. System 3 was unable to pick up feature 3, whereas systems 1 and 2 performed equally. Conclusion: En face OCT imaging has the potential to identify tumour tissue from healthy tissue. It also showed correlation with corresponding histopathologic findings. Non-contact OCT imaging of the skin is a non-invasive and convenient method and can be useful for demarcating BCCs on the face and eyelids. Future larger studies on in vivo BCCs using en face ultra-high–resolution OCT should provide information on subtyping BCCs.